2011
DOI: 10.1097/dad.0b013e3181ee547c
|View full text |Cite
|
Sign up to set email alerts
|

A Case of H Syndrome Showing Immunophenotye Similarities to Rosai–Dorfman Disease

Abstract: H syndrome (OMIM 612391) is a recently described autosomal recessive genodermatosis characterized by indurated, hyperpigmented, and hypertrichotic skin and systemic manifestations including hepatosplenomegaly, cardiac anomalies, hearing loss, hypogonadism, low height, hypertriglyceridemia, hallux valgus, and flexion contractures. H syndrome results from mutations in the SLC29A3 gene, which encodes the human equilibrative nucleoside transporter hENT3. The cutaneous histopathology is characterized by a striking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 15 publications
1
34
0
Order By: Relevance
“…The cutaneous findings and histopathology were consistent with H syndrome 4, 5. Molecular studies performed on peripheral blood revealed a recurrent mutation c.G1309>A, which is expected to lead to glycine‐to‐arginine substitution in hENT3 (p.Gly437Arg) 1, 3, 6.…”
Section: Casementioning
confidence: 60%
See 2 more Smart Citations
“…The cutaneous findings and histopathology were consistent with H syndrome 4, 5. Molecular studies performed on peripheral blood revealed a recurrent mutation c.G1309>A, which is expected to lead to glycine‐to‐arginine substitution in hENT3 (p.Gly437Arg) 1, 3, 6.…”
Section: Casementioning
confidence: 60%
“…Associated systemic manifestations include hepatosplenomegaly, congenital cardiac anomalies, hearing loss, hypogonadism, short stature, and hyperglycemia. H syndrome is caused by mutations in the gene SLC29A3 which encodes hENT3, a member of the human equilibrative nucleoside transporter family 1, 2, 3, 4, 5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our case describes the abnormal immunological findings that may be present in SLC29A3 spectrum disorders. This has rarely been explicitly reported despite the observation that autoimmune conditions such as haemolytic anaemia [3,4] and pancytopenia [5] may be associated with the syndrome. To date we could only find three other cases which characterized the immune system in affected patients.…”
Section: H Syndrome 4 Pigmented Hypertrichosis With Insulin-dependenmentioning
confidence: 99%
“…They are all caused by homozygous or compound heterozygous mutation in the SLC29A3 gene on chromosome 10q22, hence they are also called SLC29A3 spectrum disorders (1)(2)(3)(4)(5)(6). Their clinical features are summarised in Figure 1.…”
Section: H Syndrome 4 Pigmented Hypertrichosis With Insulin-dependenmentioning
confidence: 99%